Playing with verses: a study of Carnival music from the 20s to the 70s - Zupiroli, Daniela Bonamigo (Instituto de Ciências Sociais da Universidade de Brasília, 2013)
The article analyzes the carnival music during the period from the 20s to the 70s, focusing on the compositions known as carnival marches that deal with the critique of everyday life (whether by way of irony about the economy, society or even the dominant moral). The main objective is to reflect on the issue of the marches under the light of their recognition as just moments of social escapism or as belonging to a broader universe of reflection and change in society through the instigation of behavior by their memorable and transgressive lyrical.